2017
DOI: 10.1007/s12640-017-9846-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal-Spatial Profiling of Pedunculopontine Galanin-Cholinergic Neurons in the Lactacystin Rat Model of Parkinson’s Disease

Abstract: Parkinson's disease (PD) is conventionally seen as resulting from single-system neurodegeneration affecting nigrostriatal dopaminergic neurons. However, accumulating evidence indicates multi-system degeneration and neurotransmitter deficiencies, including cholinergic neurons which degenerate in a brainstem nucleus, the pedunculopontine nucleus (PPN), resulting in motor and cognitive impairments. The neuropeptide galanin can inhibit cholinergic transmission, while being upregulated in degenerating brain regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…In our previous studies [10][11][12][13], we demonstrated that the unilateral nigral lactacystin model of PD not only produced a partial lesion of the DAergic nigrostriatal pathway, but also cholinergic neuronal loss in the PPN, thereby mirroring what is observed in PD patients, and hence highlighting the suitability of this model for the current study. Intracranial injections of ChAT::Cre rats with hM3Dq DREADD were carried out while the animal remained anesthetized for the lesion surgery ( Fig.…”
Section: Laboratory Animals and Experimental Modelsupporting
confidence: 66%
See 1 more Smart Citation
“…In our previous studies [10][11][12][13], we demonstrated that the unilateral nigral lactacystin model of PD not only produced a partial lesion of the DAergic nigrostriatal pathway, but also cholinergic neuronal loss in the PPN, thereby mirroring what is observed in PD patients, and hence highlighting the suitability of this model for the current study. Intracranial injections of ChAT::Cre rats with hM3Dq DREADD were carried out while the animal remained anesthetized for the lesion surgery ( Fig.…”
Section: Laboratory Animals and Experimental Modelsupporting
confidence: 66%
“…Low-frequency DBS can be targeted to the pedunculopontine nucleus (PPN), leading to an improvement in motor-related symptoms, particularly gait and postural abnormalities, which affect a significant number of PD patients [2][3][4][5]. The PPN, located in the dorso-lateral mesopontine tegmentum, is a highly heterogeneous neuronal structure, primarily composing of cholinergic, glutamatergic, and gamma-aminobutyric acid (GABA)ergic neurons [6][7][8][9][10][11][12][13]. Clinical interest in the PPN as a DBS target stems from the partial denervation of PPN cholinergic neurons (where in the intact brain, such neurons innervate the basal ganglia motor loop [9,14]) observed in Puneet K. Sharma…”
Section: Introductionmentioning
confidence: 99%
“…The above animal models focus on recapitulating the loss of dopaminergic neurons from the substantia nigra; a recent animal model however, has concentrated on the cholinergic system in PD [109,110] . This model utilises stereotactic injection of lactocystin in the substantia nigra pars compacta, however the authors then concentrate on investigating the effects on the pedunculopontine nucleus, an area which is a promising target for therapy via deep brain stimulation [111] .…”
Section: Toxin-induced Modelsmentioning
confidence: 99%
“…Besides neurochemical groups based on neurotransmitter content [ 12 , 14 , 15 ], differences in distribution of calcium-binding proteins (rostrocaudal gradient of calbindin and calretinin; [ 16 ]) or the presence of certain neuropeptides (e.g., galanin, [ 5 , 17 ]) were also suggested to define subgroups of PPN neurons. NADPH diaphorase, neuronal nitric oxide synthetase (bNOS) and choline acetyltransferase were investigated as putative cholinergic PPN neuron markers [ 18 20 ], from which bNOS was recently proven to be a highly selective marker for cholinergic neurons [ 21 ].…”
Section: Introductionmentioning
confidence: 99%